Comparison of carbon stock potential of farmland trees in the midlands of Hawzen, Northern Ethiopia. Issue 1 (1st January 2021) - Hagos, Haftom; Tesfay, Girmay; Brhane, Emiru; Abrha, Haftu; Bezabh, Temesgen; Tesfay, Birhane; Yisehak, Biniyam
ABSTRACT: In addition to the provisioning and supporting ecosystem services, trees on agricultural landscape provide regulating services. Storing carbon in different carbon pools is one of the regulating services offered by trees on farm. However, the carbon storing potential varies with variation in altitudinal class. This study compared the carbon stock potential of farmland trees considering two altitudinal classes, Weina-kola (1500–2000 meter.) and Wein-dega (2000–2500 meter.) in Hawzen district, northern Ethiopia. These traditional altitudinal classes are interpreted as warm and tepid, respectively. Twelve farm sample plots having an area of half a hectare were chosen randomly from both the study sites. A total of 24 composite and 24 undisturbed soil samples were collected from the sample farm plots from 0–15 cm and 15–30 cm soil depths for soil organic carbon (SOC) and bulk density (BD) analysis, respectively. The result showed that total biomass carbon was significantly higher (p < 0.01) in farmland trees of Weina-kola than the Weina-dega. The total biomass carbon was estimated 8.43 and 3.25-ton C ha-1 in Weina-kola and Weina-dega, respectively. Total soil carbon and total carbon did not show significant variation between the two altitudinal classes. The reason for this could be the differences in soil types, environmental variables and management regimes. Hence, this study concluded that altitudinal variation determines the type, number and size of trees grew in each class and brought significant difference in total biomass carbon stored in farmland trees.